Community organizations and educational development among Muslims: Lessons from the 'Kerala Experience'. Issue 1 (2nd January 2021) - Alam, Mohd. Sanjeer
ABSTRACT: The overall image of Indian Muslims today is of a community deprived of a minimally decent life, having low educational attainment and experiencing socio-cultural stagnation. But, interestingly, Kerala's Muslims stand out in sharp contrast to their counterparts in most parts of the country as they are doing well, not just in education, but in most other aspects of life as well even as a century ago they were put in a defined image box and appeared to represent a community steeped in illiteracy and poverty. Equally interesting is their story of overcoming barriers to socioeconomic and educational development at the heart of which is the role played by social agencies though not fully captured in the available literature. Against this backdrop, the present paper aims to bring into sharp focus the role of social agencies, notably non-political community organizations, in shaping educational development among Kerala's Muslims. By foregrounding the 'Kerala Experience', this paper argues that structural barriers to education of a community, Muslims in the present case, are neither fixed nor immutable. It is possible for Muslims to address their educational backwardness by themselves through sustained, engaged and organized forms of efforts. The paper also discusses the lessons from the Kerala Experience and ask if the 'Kerala Model' is worth emulating for overcoming educational backwardness of Muslims in other parts of the country. Key words: community organization, education, Kerala, Mappila, Muslims, voluntary organizations.